Pengaruh Pemberian Pupuk Organik Terhadap Kandungan Karbon Organik, Nitrogen Total Tanah Dan Hasil Tanaman Jagung (Zea Mays L.) Pada Inceptisols: The Effect of Organic Fertilizer Application on Organic Carbon Content, Total Soil Nitrogen and Corn (Zea Mays L.) Yield in Inceptisols - Emma Trinurani Sofyan; Yulyanti (Universitas Widya Gama Mahakam, 2023)
The use of fertilizers as additional nutrition for maize plants needs attention. One of the efforts to optimal this problem is the use of organic fertilizer. This research aimed to study the effect of organic fertilizer application on organic carbon, total nitrogen and maize (Zea mays L.) yield in Inceptisols. The research was conducted at The Laboratory of Soil Chemistry and Plant Nutrition, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor from June up to November 2022. The design used was Randomized Block Design (RBD) with nine treatments and three replications: (A) Control, (B) NPK, (C) 1OF, (D) ¾NPK + ¾OF, (E) ¾NPK + 1OF, (F) ¾NPK + 1½OF, (G) 1NPK + ¾OF, (H) 1NPK + 1OF, (I) 1NPK + 1½OF. The results showed that the use of Organik fertilizer had a significant effect on soil organic carbon, soil total nitrogen, and maize yield components compared to the control (without fertilizer) and NPK standard. The ¾ of organic fertilizer (3.75 kg/ha) effectively increased maize yield when mixed with the NPK dose of standard fertilizer at ¾ (262.5+75+37.5 kg/ha). The use of organic ertilizer at that dose can also reduce NPK usage in Inceptisols. Keywords: Organic Fertilizer, C-Organic, N-Total, Sweet Corn, Inceptisol